Pengaruh Motivasi, Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Puskesmas Karangbahagia Di Kabupaten Bekasi - Yuni Tansri; Yulianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Performance is the qualitative and quantitative work results carried out by an employee in carrying out his work in accordance with the responsibilities given. Performance refers to the services provided or the results of work, both in terms of quality and quantity of work and can be billed according to the role of the employee in an organization or company and the employee's ability to complete his work. This study aims to evaluate the influence of motivation, workload and work environment on employee performance at the KarangBahagia Health Center in Bekasi Regency. The population in this study was conducted on KarangBahagia Health Center employees totaling 32 ASN. The sample studied was 30 ASN employees. The sampling technique used in this study was Saturated Sampling. Data were collected through interviews and questionnaires. This type of research is associative quantitative research or research that asks about the relationship between two or more variables. The relationship used in this study is causal. A causal relationship is a cause and effect relationship consisting of independent variables (variables that influence) and dependent variables (variables that influence). This research process is deductive and the technique used is inferential statistics.The results of the study indicate that motivation and work environment have a positive and significant effect on the performance of employees at the KarangBahagia Health Center. In other words, the better the motivation and work environment, the better the performance of the employees. While at the KarangBahagia Health Center, workload has a negative and significant effect on employee performance. In other words, the more the workload increases, the lower the employee performance will be. Things that need improvement include the need for rewards such as bonuses and promotions for employees who excel to increase employee motivation, the use of effective work standards to reduce the burden on employees in carrying out their work, such as the availability of complete work equipment to support their performance. It is hoped that further research will not only focus on the factors studied in this study, namely motivation, workload and work environment, but also add other factors that may affect employee performance.